Fermented rice germ extract with high concentration of gamma-aminobutyric acid enhances pentobarbital-induced sleep via GABAergic system in rats - Minsook Ye; Woojin Jeong; Hyo Jeong Yu; Kyoung-min Rheu; Bae-jin Lee; Insop Shim (PLoS ONE, 2025)
In modern societies, insomnia stands out as a widespread health concern. Gamma-aminobutyric acid (GABA), an inhibitory neurotransmitter, can exert hypnotic effects. However, despite various clinical trials conducted, scientific evidence regarding the impact of ingested GABA on sleep remains unclear. Therefore, in this study, we investigated the sedative effects of fermented rice germ (RG30) extract with a high GABA concentration through electroencephalography (EEG) analysis in a pentobarbital-induced sleep animal model. The exploration into the neural basis of these positive effects involved evaluating orexin, GABAA receptor, and serotonin (5-HT) immunoreactivity in the brain using immunohistochemical methods. Furthermore, we conducted a binding assay for GABAA receptors and 5-HT2C receptors, as these are considered pivotal targets in the mechanism of action for sleep aids. In the binding assay, RG30 displayed binding affinity to the GABAA receptor (IC50 value of 5.911 µg/mL) and 5-HT2C receptor (IC50 value of 56.89 µg/mL). Administration of RG30 increased NREM sleep time and reduced wake time in a pentobarbital-induced sleep model. Low-dose RG30 (RG30_L; 40 mg/kg) induced significant alterations in EEG-defined sleep architecture, whereas high-dose RG30 (RG30_H; 90 mg/kg) predominantly modulated orexin expression in the lateral hypothalamus and GABAA receptor levels in the ventrolateral preoptic nucleus. No significant changes were observed in 5-HT expression within the dorsal raphe nucleus. In conclusion, RG30 increased NREM sleep and significantly improved sleep behavior due to its action on the GABAA receptors. The collective findings suggest that RG30 could be considered as a novel sleep-enhancing agent in pharmaceutical and food industries.